Principals’ Digital Leadership Competencies in the Fourth Industrial Revolution: Teachers’ Perspectives - John Olayemi Okunlola; Suraiya Rathankoomar Naicker (Education Sciences, 2025)
As the Fourth Industrial Revolution (4IR) reshapes society, digital leadership in education becomes crucial. This study explores teachers’ perspectives on high school principals’ digital leadership competencies in Oyo State, Nigeria, a region grappling with the digital divide. This offers a counterpoint to research in high-income countries. Using a quantitative, descriptive research design, 381 teachers across three senatorial districts were selected via multi-stage sampling. The study addressed one research question and tested two hypotheses. Data were collected using the High Schools’ Digital Leadership Standards Questionnaire (HSDLSQ). The reliability coefficients ranged from α = 0.85 to 0.91 across five domains: visionary leadership, digital learning culture, professional development, systemic improvement, and digital citizenship. Descriptive statistics (percentages, mean, and standard deviation) and inferential statistics (independent t-test) were used for analysis at a 0.05 significance level. The findings revealed that high school leaders possess the skills to meet the ISTE-A digital leadership standards set by the International Society for Technology in Education (ISTE). Female leaders exhibited slightly higher digital skills than males, though gender was insignificant in meeting the ISTE-A standards overall. The study underscores the importance of digital leadership in school management, offering practical implications for leadership practices, policy decisions, and future research. Although the ISTE-A standards are met, the emphasis on systemic improvement highlights how Nigerian principals adapt strategies to local resource constraints, differing from high-tech education systems. Recommendations include promoting the ISTE-A standards among school leaders, investing in digital leadership training, fostering digital literacy, and supporting adaptability to technological changes to advance digital transformation in education.